Protecting Our Seas - Marine Environmental Governance in the South China Sea - Rini Astuti (2017)
By meeting the UN’s Sustainable Development Goal 14 on Life Below Water, parties in the South China Sea can enhance transboundary partnerships for a more sustainable approach to marine environmental governance.